Character Education of Cultural Art Subjects Through Purwa Wayang Kulit Media: Perception Study of Teachers of Middle School in Cultural Arts in Solo Raya Region - Subiyantoro, Slamet; Fadhilah, Siti S (PINUS: Jurnal Penelitian Inovasi Pembelajaran, 2019)
This study reveals the cultural arts of teachers on local media shadow pupils to instill character values through learning arts and culture in junior high schools in the Solo Raya region. During this time, pure shadow pupils were only used as public performances outside formal such as junior high school institutions. While the teachers in instilling the value of character education through teaching are still limited to formal tools. This research has its own specificity because of the use of the wayang kulit media. This research was carried out by a number of teachers in the entire city of Solo, which covered 7 (seven) regencies/municipalities. The technique for collecting data is done by questionnaires and interviews. To analyze the data using the initial steps of data collection, data reduction, data presentation, and drawing conclusions. The results showed that most of the cultural teachers had positive learning from students in junior high school. However, most people who have an undergraduate education are positive perceptions. Because the wayang kulit purwa has the contents of moral values, social culture, character education and love for the motherland.